Vet an action play book - Green , Dan (London Ladybird Books, 2020)
It's another busy day! Join in and use the flaps to help the vet as she listens to the dog's heart, gives the chameleon her medicine and X-rays the cat's leg. With interactive action-flaps, you can do it, too!
Scientific notions
Keywords: Animals; Science